Experimental and numerical study of the motion of non-spherical particles in wall-bounded turbulent flows (2007)
This book compiles the obtained results in the research project entitled “Estudio Experimental y Modelización del Movimiento de Partículas no Esféricas en un Flujo Turbulento y su Interacción con Paredes Sólidas” developed jointly by the Grupo de Investigación en Mecánica de Fluidos FMRG de la Universidad Autónoma de Occidente, Cali (Colombia) and the chair of Mechanical Processes of the Zentrum für Ingenieurwissenschaten of Martin-Luther Universität Halle- Wittenberg (Germany). The financial support of the Dirección de Investigaciones y Desarrollo Tecnológico of the Universidad Autónoma de Occidente through the project “Estudio Experimental y Modelización del Movimiento de Partículas no Esféricas en un Flujo Turbulento y su Interacción con Paredes Sólidas” is gratefully acknowledged. Also, it is necessary to acknowledge the support of the Deutsche Forschung Gemeinschaft through the contracts So 204/1-2 and the worth collaboration of Dr. J. Kussin and Eng. A. Hölzer